Implementasi Sistem dalam Menghitung Transaksi dan Stok pada Proses Penjualan di Yamaha Anugerah Motor Berbasis Web - Wijaya, Stanley; Birowo, Sigit (Global Research on Economy, Business, Communication, and Information, 2023)
The rapid development of technology in the era of Industry 4.0 has made various internet uses essential to fulfill several needs. This includes systems that can assist in the business sector. With the advancement of technology, it greatly aids daily life. The research aims to develop a web-based application to calculate transactions and stock in business. This application can display information related to sales figures, reports, and data management of goods that are user-friendly for business practitioners. The system to calculate transactions and stock can be applied to assist the sales business process. It provides information about available items so that business practitioners can sell goods and view transaction data. This web-based system is operated through a website and uses the internet as a platform to manage and store available data. Researchers used qualitative field research methods to collect profile data and information about the current running systems as supporting elements in application development. For application design, researchers used Visual Studio Code software, which can be used to create websites using programming languages such as HTML, CSS, and JavaScript. The system development method applied is the prototype method. This method was chosen by researchers as it is suitable and meets the needs of the system to be developed. The final result of this research is a web-based application for calculating transactions and stock in the sales process at Yamaha Anugerah Motor. The designed application features displaying information about managing goods and categories, as well as conducting transactions that are directly recorded in sales reports. With this system, one can track transactions and stock levels. Data management for goods is computerized, and reports about transactions and stock can be printed easily. It also facilitates easy restocking of goods.